Impact of smoking habit on baseline and on-treatment platelet reactivity in STEMI patients treated with 3rd generation P2Y12. (14th October 2021) - Canonico, M E; Scudiero, F; Sanna, G D; Siciliano, R; Guarino, S; Saba, P S; Esposito, G; Parodi, G
Abstract: Background: Smoking habit is a well known risk factor for cardiovascular disease. High on-treatment platelet reactivity has been associated with high risk of ischemic events in STEMI patients. The relationship between platelet reactivity and smoking habit was investigated only in few studies, and the impact of smoke on platelet reactivity in STEMI patients treated with 3rd generation P2Y12 inhibitor is still lacking. Purpose: This study aim to assess the impact of smoking habits on baseline and on-treatment platelet reactivity in STEMI patients treated with 3rd generation P2Y12 inhibitor. Methods: Overall, 429 STEMI patients were enrolled in this study. Patients were divided into two groups according to smoking habit. Platelet reactivity was assessed by VerifyNow at baseline and after 3rd generation P2Y12 inhibitor (ticagrelor or prasugrel) loading dose (LD). Blood samples were obtained at baseline (T0), and after 1 hour (T1), 2 hours (T2), 4–6 hours (T3) and 8–12 hours (T4) after LD. Results: The mean age of the enrolled population was 62±12 and male rate was 75%. Patients with smoking habit were younger (75.8% vs 38.9%, p<0.001 for age <65 years), with higher prevalence of family history of CAD, while with a lower rate hypertension (43.4% vs 65.9%, p<0.001) and previous myocardial infarction (5.3% vs 11.4%, p=0.022) (Table). Smoker patients had lower platelet reactivity either at baseline [T0: 249 (205–285) vs 284 (230–324), p<0.001] or at 2 hours after the LD [T2: 107 (18–279) vs 136 (51–260), p=0.003] (Table). Similarly, Smoker patients experienced a lower rate of in-hospital composite adverse event of death, reinfarction, stroke or acute kidney injury (1.6% vs 12.4%; p≤0.001) (Table). Multivariate analysis demonstrated that left ventricular ejection fraction at admission (OR= 0.916, 95% CI 0.865–0.969; p=0.002), and platelet reactivity at baseline (OR= 1.013, 95% CI 1.002–1.024; p=0.024) were independent predictors of in-hospital composite adverse event. Conclusions: Smoker status is associated with lower platelet reactivity either at baseline or after LD and with a better short-term prognosis in STEMI patients treated by dual antiplatelet therapy with ticagrelor or prasugrel. FUNDunding Acknowledgement: Type of funding sources: None.